2009
DOI: 10.1177/154193120905301822
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Presentation of AdSense Ads within Blogs

Abstract: AdSense text ads have become a popular method of advertising on the web, specifically within blogs when using Blogger. With increasing popularity of blogs, AdSense ads are enticing to bloggers because they offer financial rewards with relatively little effort. The biggest challenge with AdSense is generating revenue through clicks or impressions. Google offers tips on optimal presentation for ads to generate higher revenue, but empirical evidence is lacking in this area. Thus, the purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Fox, Smith, Chaparro, and Shaikh (2009) suggest that adverts should be located high on the page and use a contrasting color scheme. By maximizing visibility, adverts are expected to build brand recognition and it is suggested that this increased recognition will result in increased click rates (Fox et al, 2009). However, for pay-per-click adverts, brand recognition alone is not sufficient to generate revenue for the website publisher.…”
Section: Introductionmentioning
confidence: 98%
“…Fox, Smith, Chaparro, and Shaikh (2009) suggest that adverts should be located high on the page and use a contrasting color scheme. By maximizing visibility, adverts are expected to build brand recognition and it is suggested that this increased recognition will result in increased click rates (Fox et al, 2009). However, for pay-per-click adverts, brand recognition alone is not sufficient to generate revenue for the website publisher.…”
Section: Introductionmentioning
confidence: 98%